Słowem po mapie (umysłu i czasu). Wybrane przestrzenie w tekstach Pablopavo - Czaja, Kamila (Zagadnienia Rodzajów Literackich, 2023)
Starting with Warsaw themes in the works of Pablopavo (Paweł Sołtys) — which have dominated previous research papers — the article signalizes their role in describing not only them rapidly changing city itself, but also its inhabitant’s sense of inadequacy. Most of all, the analysis of the songs from different albums, from Telehon (2009) to Mozaika (2022), and from different musical projects (Pablopavo solo, the band Pablopavo i Ludziki, Pablopavo recording with Naprawdę Duży Zespół, with Praczas or with Praczas and Anna Iwanek) deals with motifs not discussed before, e.g. the vision of home, that can be a shield against the evil world, but can have the dark side or be used as a way to show the duality of the human mind. The metaphors created by Pablopavo are also interpreted in the article: the conceptual metaphors, as the versions of the structural metaphor LIFE IS A JOURNEY (a turn, an elevator, a railway station, a map), the orientational metaphors (mixing the dimensions) and the metaphors that blend space and time. The reflections profi led this way reveal the potential of these topics and figures in straightening out the mind and the memories, as well as in identifying the human position in space — the space understood more in terms of existence as space.